2018
DOI: 10.1021/acs.macromol.8b01943
|View full text |Cite
|
Sign up to set email alerts
|

Detection of PLP Structure for Accurate Determination of Propagation Rate Coefficients over an Enhanced Range of PLP-SEC Conditions

Abstract: The factors influencing the periodic structure in molar mass distributions (MMDs) generated in pulsed-laser polymerization (PLP) experiments are investigated to extend the range of operating conditions under which radical polymerization propagation rate coefficients (k p) can be reliably estimated. Specifically, it is shown how k p may be determined well into conditions corresponding to the so-called low and high termination rate limits. A new parameter x is introduced to provide a convenient measure of when P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…polymerization processes, the propagation rate coefficient, k p , and the termination rate should be accurately known. [10][11][12] The well-established method for k p determination is pulsed-laser polymerization in conjunction with size-exclusion chromatography, PLP-SEC. [13] The k p value is obtained from maxima L i of the firstderivative curve of the molar weight distribution (MWD) measured on the product from polymerization induced by a photoinitiator under periodic laser pulsing at a precisely known laser pulse repetition rate (p.r.r.…”
Section: Doi: 101002/macp201900345mentioning
confidence: 99%
See 2 more Smart Citations
“…polymerization processes, the propagation rate coefficient, k p , and the termination rate should be accurately known. [10][11][12] The well-established method for k p determination is pulsed-laser polymerization in conjunction with size-exclusion chromatography, PLP-SEC. [13] The k p value is obtained from maxima L i of the firstderivative curve of the molar weight distribution (MWD) measured on the product from polymerization induced by a photoinitiator under periodic laser pulsing at a precisely known laser pulse repetition rate (p.r.r.…”
Section: Doi: 101002/macp201900345mentioning
confidence: 99%
“…For poly(PnMA), T g is estimated from dynamic mechanical analysis to be around 20 °C (see Figure S1, Supporting Information), which suggests that poly(PnMA) should be an attractive polymer for materials, including polymer nanocomposites and (block) copolymers, used at ambient temperature. For the design of polymerization processes, the propagation rate coefficient, k p , and the termination rate should be accurately known . The well‐established method for k p determination is pulsed‐laser polymerization in conjunction with size‐exclusion chromatography, PLP–SEC .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laser frequencies up to 100 Hz were used in most of the above-mentioned PLP-SEC experiments. Nevertheless, accurate estimation of k p from a PLP experiment is still a challenge [9]. However, the PLP-shape of the MMD (distributions with clearly defined critical points) was not obtained for acrylic monomers, specifically for n-butyl acrylate at temperatures ≥30 • C. Although it was found that by carrying out the PLP reaction at sufficient low temperatures the PLP-MMD was recovered, the origin of this phenomena was not known initially [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…[5,8] For specific applications, such as coatings, MMD bimodality has even been put forward as the primary target, leading to dispersity values higher than 4. [15][16][17] For the determination of the radical propagation, [18][19][20][21][22][23] backbiting, [24][25][26][27] and β-scission [24,28] rate coefficients or the quantification of photo dissociation quantum yields, [29] a modulated MMD trace is beneficial. In contrast to modulated and broad MMDs, the more recent chemical development of living and reversible deactivation radical poly merization (L/RDRP) mechanisms has made clear that more niche applications (e.g., drug delivery or high-end cosmetics) can benefit from lower M m values (e.g., 10 4 g mol −1 ) and narrow monomodal MMDs with Ð values below 1.5.…”
mentioning
confidence: 99%